Secuelas emocionales en adultas jóvenes abusadas sexualmente en su infancia. - Maldonado Guerra, Laura (Revista Psicólogos, 2013)
<span data-sheets-value="{"1":2,"2":"This study aimed, through qualitative research, to establish the emotional scars on\r sexually abused children, now young adults. The sample was conformed by five women between\r the ages 23 -30, two of them referred by Fundación Sobrevivientes and the rest by private clinics.\r The instrument used to collect the data was a semi-structured interview developed by the researcher\r and validated by experts. The data was analyzed through a discussion of the results, tables of\r indicators and sense matrix. As a conclusion, the major sequels of sexual abuse children that the\r participants manifested are: a state of dysphoria characterized by persistent sadness, anxiety and\r irritability, thoughts of hurting their selves or harming others, fear, and difficulty to express or receive\r displays of tenderness and intimacy. The recommendations were addressed especially to mental\r health professionals."}" data-sheets-userformat="{"2":8705,"3":{"1":0},"12":0,"16":14}">This study aimed, through qualitative research, to establish the emotional scars on sexually abused children, now young adults. The sample was conformed by five women between the ages 23 -30, two of them referred by Fundación Sobrevivientes and the rest by private clinics. The instrument used to collect the data was a semi-structured interview developed by the researcher and validated by experts. The data was analyzed through a discussion of the results, tables of indicators and sense matrix. As a conclusion, the major sequels of sexual abuse children that the participants manifested are: a state of dysphoria characterized by persistent sadness, anxiety and irritability, thoughts of hurting their selves or harming others, fear, and difficulty to express or receive displays of tenderness and intimacy. The recommendations were addressed especially to mental health professionals.